THRIFT FASHION TRENDS AS A NEW CULTURE OF CONSUMERISM - Sulissya Nur Syafa'ati; Johny Alfian Khusyairi (Airlangga Development Journal, 2024)
The mushrooming phenomenon of fashion thrift in Indonesia has resulted in a new culture. The new culture is the consumption of young people on thrift fashion products. This research uses the qualitative descriptive method. The data was taken by filling out an open questionnaire to 10 respondents obtained through Instagram social media. The data obtained were then analyzed using the theory of the consumption society by Jean P. Baudrillard where the consumption of fashion thrift products not only pays attention to the value of the function of a garment but also the value of symbols in purchasing fashion thrift products. The results of this study show that the reasons respondents consume fashion thrift are because they accidentally found suitable products, complete collections, low product prices, products that are sold well and even some are products with well-known brands, and pride factors.